2012
DOI: 10.4081/idr.2012.e30
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of HIV-1 in Cerebrospinal Fluid and Plasma in Cryptococcal Meningitis

Abstract: In order to determine HIV-1 kinetics in cerebrospinal fluid (CSF) and plasma in patients with cryptococcal meningitis (CM), we undertook a prospective collection of paired CSF/plasma samples from antiretroviral therapy-free HIV-infected patients with CM. Samples were obtained at baseline (S1) and at the second (S2) and third (S3) weeks of antifungal therapy. HIV-1 CSF concentrations were significantly lower in both S2 and S3 with respect to S1. Plasma concentrations remained stable. HIV-1 concentrations were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The HIV-1 VL was comparable between the compartments at the first two time points but higher in plasma than CSF on day 14, mainly due to a decrease in CSF HIV-1 VL. One study reported significantly higher HIV-1 VL in plasma than CSF at all three-time points [ 38 ]. In another study where the CSF and plasma HIV-1 VL were compared on days 1 and 14, plasma HIV-1 VL was reported to be higher than CSF HIV-1 VL on both days [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 VL was comparable between the compartments at the first two time points but higher in plasma than CSF on day 14, mainly due to a decrease in CSF HIV-1 VL. One study reported significantly higher HIV-1 VL in plasma than CSF at all three-time points [ 38 ]. In another study where the CSF and plasma HIV-1 VL were compared on days 1 and 14, plasma HIV-1 VL was reported to be higher than CSF HIV-1 VL on both days [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…75 Whether HIV replication in the brain is independent of replication in plasma of patients with OI is still a matter of debate. The finding of high levels of divergent human immunodeficiency virus 1 (HIV-1) quasispecies, higher viral loads in opportunistic neurological infections that are independent of plasma viral load and CD4 count, 72,76 and different viral kinetics of HIV-1 in the CSF 77 implies that there is a local source of HIV in the brain that could influence both neurological disease occurrence and outcomes.…”
Section: General Concept: Hiv Is Not Lonely In the Brainmentioning
confidence: 99%
“…The most impaired cognitive domains were psychomotor, learning, and memory for neurotoxoplasmosis survivors and psychomotor and speed of information processing for PML survivors. Patients with OIs without significant brain destruction, such as CNM, may present a spontaneous decline in HIV CSF viral load 77 following acute infection and may also improve their cognitive function after an initial significant short-term decline. 79 Interestingly, a recent study described significant deficits in neurocognitive function in advanced HIV/AIDS individuals with positive C neoformans antigenemia in CSF but with no meningitis that improved after initiation of preemptive fluconazole treatment and cART.…”
Section: General Concept: Hiv Is Not Lonely In the Brainmentioning
confidence: 99%